Nickel plating modified neodymium iron boron permanent magnet material and preparation method thereof

By composite treatment of magnetron sputtering Al-Ga layer, electrophoretic deposition of TbF3 layer and electroplating of NI-Co-Tb layer on the surface of NdFeB permanent magnet material, the problem of decreased corrosion resistance in the existing technology is solved, and the magnetic properties and corrosion resistance are improved.

CN120674226AActive Publication Date: 2025-09-19JIANGXI YG MAGNET CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511039339.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-28
Publication Date
2025-09-19
Estimated Expiration
2045-07-28

AI Technical Summary

Technical Problem

In the process of improving the coercive force performance of NdFeB permanent magnet materials, the existing technology easily leads to a decrease in corrosion resistance, and the existing method may cause oxidation of heavy rare earth elements or absorption of hydrogen ions, affecting the overall performance of the material.

Method used

A composite treatment method of magnetron sputtering Al-Ga layer, electrophoretic deposition of TbF3 layer and electroplating of NI-Co-Tb layer is adopted. The Al-Ga layer enhances the adhesion between the coating and the substrate, the TbF3 layer improves the grain boundary phase structure, and the NI-Co-Tb layer improves the density and bonding performance of the coating.

Benefits of technology

It significantly improves the magnetic properties and corrosion resistance of NdFeB permanent magnet materials, enhances the adhesion and uniformity of the coating, reduces the risk of hydrogen embrittlement, and improves the coercive force and remanent magnetic properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a nickel plating modified neodymium iron boron permanent magnet material and a preparation method thereof, and relates to the technical field of permanent magnet materials. The nickel plating modified neodymium-iron-boron permanent magnet material specifically comprises the following steps that S1, the neodymium-iron-boron permanent magnet material is sequentially subjected to grinding, polishing, washing, drying and Al-Ga layer magnetron sputtering, and a neodymium-iron-boron permanent magnet material A is obtained; s2, sequentially carrying out polishing, washing, drying, electrophoretic deposition of a TbF3 layer and thermal diffusion treatment on the neodymium-iron-boron permanent magnet material A to obtain a neodymium-iron-boron permanent magnet material B; and S3, electroplating an NI-Co-Tb layer on the surface of the neodymium-iron-boron permanent magnet material B to obtain the nickel-plated modified neodymium-iron-boron permanent magnet material. According to the preparation method provided by the invention, the magnetic performance and the corrosion resistance of the permanent magnet material are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of permanent magnetic materials, in particular to a nickel-plated modified neodymium iron boron permanent magnetic material and a preparation method thereof. Background Art

[0002] NdFeB permanent magnets, due to their excellent magnetic properties, are widely used in electronics, automotive, energy, and other fields, making them one of the most widely used rare earth permanent magnet materials. While the remanence and maximum energy product of NdFeB permanent magnets are approaching their theoretical limits, their coercivity is generally only half of the theoretical value. Therefore, improving coercivity without compromising remanence and maximum energy product is a key issue.

[0003] In the prior art, grain boundary diffusion is often performed by introducing heavy rare earth elements, which can significantly enhance the magnetocrystalline anisotropy at the grain boundaries, thereby improving the coercivity of the magnet. However, this method requires the pre-preparation of a diffusion source coating on the substrate surface. However, commonly used methods, such as metal slurry, may cause oxidation of the heavy rare earth elements during the debonding or solvent evaporation process, reducing the performance of the magnet. The hydrogen ions generated by the electroplating process are easily absorbed by the NdFeB material, resulting in a decrease in corrosion resistance. Patent No. CN116544022A discloses a method for improving the performance of NdFeB magnets and a high-coercivity NdFeB magnet. The method uses ferromagnetic alloy diffusion source powder to be deposited on the surface of a magnetized or magnetized NdFeB magnet under magnetic adsorption to obtain a magnet to be diffused, and then performs grain boundary diffusion. However, since the substrate needs to be magnetized in advance, this may cause internal stress to increase during grain boundary diffusion, resulting in microcracks and a decrease in corrosion resistance.

[0004] In summary, it is of great significance to solve the above problems and prepare a NdFeB permanent magnet material with good magnetic properties and corrosion resistance. Summary of the Invention

[0005] The object of the present invention is to provide a nickel-plated modified NdFeB permanent magnet material and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A method for preparing a nickel-plated modified NdFeB permanent magnet material comprises the following steps:

[0008] S1: grinding, polishing, washing, drying, and magnetron sputtering Al-Ga layers on the NdFeB permanent magnet material to obtain NdFeB permanent magnet material A;

[0009] S2: grinding, washing, drying, electrophoretically depositing a TbF3 layer on the NdFeB permanent magnet material A, and performing thermal diffusion treatment to obtain the NdFeB permanent magnet material B;

[0010] S3: Electroplating a NI-Co-Tb layer on the surface of the NdFeB permanent magnet material B to obtain a nickel-plated modified NdFeB permanent magnet material.

[0011] Preferably, during the magnetron sputtering process, the target material is Al-Ga alloy and the vacuum degree is 5×10 -4 Pa, the working gas is argon, the flow rate is 35~45sccm, and the coating thickness is 0.4~0.6μm.

[0012] More preferably, the Al-Ga alloy comprises 75-85 wt % aluminum and the remainder is gallium.

[0013] Preferably, during the electrophoretic deposition process, the deposition solution comprises the following raw materials: 10-12 g / L terbium fluoride, 1-1.5 g / L magnesium chloride, and the solvent is ethanol.

[0014] Preferably, during the electrophoretic deposition process, the NdFeB permanent magnet material A is the cathode, the stainless steel plate is the anode, the distance between the cathode and the anode is 3 mm, the temperature is 25-30° C., the voltage is 100 V, and the time is 140-160 seconds.

[0015] More preferably, during the thermal diffusion process, the specific process is to -3 Under the conditions of 850~875℃ for 9~9.5h, then heat treat at 500~520℃ for 1.5~2h.

[0016] Preferably, during the electroplating process, the electroplating solution comprises the following raw materials: 220-240 g / L nickel sulfate hexahydrate, 35-40 g / L nickel chloride hexahydrate, 44-48 g / L cobalt sulfate heptahydrate, 10-12 g / L terbium nitrate hexahydrate, 1-1.5 g / L saccharin sodium, 18-22 g / L potassium chloride, 28-30 g / L boric acid, 0.1-0.2 g / L sodium dodecyl sulfate, and a pH of 4.5-5.5.

[0017] Preferably, during the electroplating process, the current density is 1.5-2 A / dm 2 , time is 25~30min, temperature is 45~50℃.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention sequentially magnetron sputters an Al-Ga layer on the surface of the NdFeB permanent magnet material, electrophoretically deposits a TbF3 layer as a composite diffusion source, and then electroplates a NI-Co-Tb layer, thereby improving the magnetic properties and corrosion resistance of the permanent magnet material.

[0019] During magnetron sputtering of the Al-Ga layer, the smaller atoms of aluminum and gallium can penetrate the surface of the NdFeB magnet material, enhancing the adhesion between the coating and the substrate, filling tiny gaps, and improving corrosion resistance. This helps prevent hydrogen ions generated during subsequent electrophoretic deposition and electroplating processes from penetrating into the interior of the substrate, causing hydrogen embrittlement. Furthermore, during the subsequent thermal diffusion process, due to the alloy's low melting point, aluminum and gallium react near the neodymium element, undergoing a eutectic reaction. This lowers the melting point of the neodymium-rich phase, improves wettability, reduces interfacial energy, and improves uniformity while increasing the material's corrosion resistance and magnetic properties.

[0020] During the electrophoretic deposition of the TbF3 layer, grain boundary diffusion is carried out using electrophoretically deposited terbium fluoride and magnetron sputtered Al-Ga layers as composite diffusion sources. During this process, aluminum and gallium effectively improve the structure of the magnet's grain boundary phase, forming a continuous grain boundary phase, promoting the diffusion of terbium into the magnet's interior, and refining the grains. Tb enters the magnet along the grain boundaries, replacing some of the neodymium in the main phase, forming a shell structure, increasing the anisotropy field, and significantly improving the magnet's coercivity with minimal degradation of remanent magnetic properties. Aluminum increases the diffusion depth of Tb and improves coercivity, while gallium refines the grains, increases the proportion of the grain boundary phase, and comprehensively improves magnetic properties. Selecting an aluminum-gallium alloy with an aluminum content of 75-85wt% maximizes the electrode potential at the grain boundaries, while modifying and stabilizing the neodymium-rich grain boundaries, significantly improving corrosion resistance and magnetic properties. The present invention selects to arrange the Al-Ga layer on the side close to the magnet. Although the grain boundary diffusion time required for terbium fluoride on the side close to the magnet material is relatively longer than that of terbium fluoride, the Al-Ga layer preferentially forms a transition environment for the diffusion of terbium, thereby increasing the diffusion depth of terbium and improving the uniformity, thereby greatly improving the coercive force of the magnet.

[0021] Among them, during the electroplating process of the Ni-Co-Tb layer, by introducing a small amount of terbium element, it can enter the lattice of the nickel-cobalt alloy layer to form a more stable alloy layer, which helps to further improve the density of the coating, reduce the corrosion current density in the corrosive environment, increase the corrosion resistance, and improve the bonding performance of the coating after thermal diffusion with the first two layers to prevent the coating from falling off. DETAILED DESCRIPTION

[0022] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0023] It should be noted that the following parts are calculated by weight, and the purchase manufacturers of all raw materials involved in the present invention are not particularly restricted, and illustratively include: aluminum gallium alloy target, provided by Hebei Ruichi New Materials Co., Ltd.; TbF3, with a particle size of 0.1~1 μm; CAS number of nickel sulfate hexahydrate: 15244-37-8; CAS number of nickel chloride hexahydrate: 7791-20-0; CAS number of cobalt sulfate heptahydrate: 10026-24-1; CAS number of terbium nitrate hexahydrate: 13451-19-9; CAS number of saccharin sodium: 128-44-9; CAS number of sodium dodecyl sulfate: 2386-53-0.

[0024] In the following examples, parts are by mass, and the above-mentioned and other raw materials used but not mentioned are commercially available.

[0025] Among them, NdFeB permanent magnet material includes the following elements: neodymium: 23.1%, praseodymium: 6.1%, boron: 1.18%, cobalt: 0.24%, and the balance is iron.

[0026] Example 1: A method for preparing a nickel-plated modified NdFeB permanent magnet material comprises the following steps:

[0027] S1: The outer surface of the NdFeB permanent magnet material was sanded to 2000 mesh with sandpaper, polished to a mirror surface with a polishing machine, ultrasonically cleaned with ethanol and acetone respectively, dried, and transferred to a vacuum chamber. Al-Ga alloy (Al-Ga alloy includes 80wt% aluminum and the rest is gallium) was used as the target material. The vacuum degree was 5×10 -4 Under Pa, argon was used as the working gas at a flow rate of 40 sccm, and an Al-Ga layer with a thickness of 0.5 μm was obtained by magnetron sputtering to obtain NdFeB permanent magnet material A;

[0028] S2: The NdFeB permanent magnet material A was polished, washed, dried, and transferred to the deposition solution. The NdFeB permanent magnet material A was used as the cathode and the stainless steel plate was used as the anode. The distance between the cathode and the anode was 3 mm. At a temperature of 2 ° C and a voltage of 100 V, a TbF3 layer was electrophoretically deposited for 150 seconds. The material was washed, dried, and placed in a vacuum of 2.5×10 -3 The NdFeB permanent magnet material B is obtained by first heat treating at 860°C for 9 hours and then heat treating at 510°C for 2 hours; wherein the preparation method of the deposition liquid is to add terbium fluoride and magnesium chloride to anhydrous ethanol and ultrasonically disperse them for 30 minutes to obtain a deposition liquid including 10 g / L terbium fluoride and 1.5 g / L magnesium chloride;

[0029] S3: On the surface of NdFeB permanent magnet material B, the current density is 1.5A / dm 2, electroplating at a temperature of 50°C for 30 minutes to form a NI-Co-Tb layer, and annealing at 510°C for 2 hours to obtain a nickel-plated modified NdFeB permanent magnet material; wherein the electroplating solution includes the following raw materials: 230g / L nickel sulfate hexahydrate, 36g / L nickel chloride hexahydrate, 46g / L cobalt sulfate heptahydrate, 10g / L terbium nitrate hexahydrate, 1g / L saccharin sodium, 20g / L potassium chloride, 30g / L boric acid, 0.1g / L sodium dodecyl sulfate, and the pH is 5.

[0030] Example 2: The preparation method of nickel-plated modified NdFeB permanent magnet material comprises the following steps:

[0031] S1: The outer surface of the NdFeB permanent magnet material was sanded to 2000 mesh with sandpaper, polished to a mirror surface with a polishing machine, ultrasonically cleaned with ethanol and acetone respectively, dried, and transferred to a vacuum chamber. Al-Ga alloy (Al-Ga alloy includes 75wt% aluminum and the rest is gallium) was used as the target material. The vacuum degree was 5×10 -4 Under Pa, argon was used as the working gas at a flow rate of 40 sccm, and an Al-Ga layer with a thickness of 0.5 μm was obtained by magnetron sputtering to obtain NdFeB permanent magnet material A;

[0032] S2: The NdFeB permanent magnet material A was polished, washed, dried, and transferred to the deposition solution. The NdFeB permanent magnet material A was used as the cathode and the stainless steel plate was used as the anode. The distance between the cathode and the anode was 3 mm. At a temperature of 2 ° C and a voltage of 100 V, a TbF3 layer was electrophoretically deposited for 150 seconds. The material was washed, dried, and placed in a vacuum of 2.5×10 -3 The NdFeB permanent magnet material B is obtained by first heat treating at 860°C for 9 hours and then heat treating at 510°C for 2 hours; wherein the preparation method of the deposition liquid is to add terbium fluoride and magnesium chloride to anhydrous ethanol and ultrasonically disperse them for 30 minutes to obtain a deposition liquid including 10 g / L terbium fluoride and 1.5 g / L magnesium chloride;

[0033] S3: On the surface of NdFeB permanent magnet material B, the current density is 1.5A / dm 2 , electroplating at a temperature of 50°C for 30 minutes to form a NI-Co-Tb layer, and annealing at 510°C for 2 hours to obtain a nickel-plated modified NdFeB permanent magnet material; wherein the electroplating solution includes the following raw materials: 220g / L nickel sulfate hexahydrate, 35g / L nickel chloride hexahydrate, 44g / L cobalt sulfate heptahydrate, 10g / L terbium nitrate hexahydrate, 1g / L saccharin sodium, 18g / L potassium chloride, 28g / L boric acid, 0.1g / L sodium dodecyl sulfate, and the pH is 5.

[0034] Example 3: The preparation method of nickel-plated modified NdFeB permanent magnet material comprises the following steps:

[0035] S1: The outer surface of the NdFeB permanent magnet material was sanded to 2000 mesh with sandpaper, polished to a mirror surface with a polishing machine, ultrasonically cleaned with ethanol and acetone respectively, dried, and transferred to a vacuum chamber. Al-Ga alloy (Al-Ga alloy includes 85wt% aluminum and the rest is gallium) was used as the target material. The vacuum degree was 5×10 -4 Under Pa, argon was used as the working gas at a flow rate of 40 sccm, and an Al-Ga layer with a thickness of 0.5 μm was obtained by magnetron sputtering to obtain NdFeB permanent magnet material A;

[0036] S2: The NdFeB permanent magnet material A was polished, washed, dried, and transferred to the deposition solution. The NdFeB permanent magnet material A was used as the cathode and the stainless steel plate was used as the anode. The distance between the cathode and the anode was 3 mm. At a temperature of 2 ° C and a voltage of 100 V, a TbF3 layer was electrophoretically deposited for 150 seconds. The material was washed, dried, and placed in a vacuum of 2.5×10 -3 The NdFeB permanent magnet material B is obtained by first heat treating at 860°C for 9 hours and then heat treating at 510°C for 2 hours; wherein the preparation method of the deposition liquid is to add terbium fluoride and magnesium chloride to anhydrous ethanol and ultrasonically disperse them for 30 minutes to obtain a deposition liquid including 10 g / L terbium fluoride and 1.5 g / L magnesium chloride;

[0037] S3: On the surface of NdFeB permanent magnet material B, the current density is 1.5A / dm 2 , electroplating at a temperature of 50°C for 30 minutes to form a NI-Co-Tb layer, and annealing at 510°C for 2 hours to obtain a nickel-plated modified NdFeB permanent magnet material; wherein the electroplating solution includes the following raw materials: 240g / L nickel sulfate hexahydrate, 40g / L nickel chloride hexahydrate, 48g / L cobalt sulfate heptahydrate, 12g / L terbium nitrate hexahydrate, 1.5g / L saccharin sodium, 22g / L potassium chloride, 30g / L boric acid, 0.2g / L sodium dodecyl sulfate, and the pH is 5.

[0038] Comparative Example 1: Based on Example 1, the magnetron sputtering method only sputters aluminum without electroplating. The other processes remain unchanged, as follows:

[0039] S1: The outer surface of the NdFeB permanent magnet material was sanded to 2000 mesh with sandpaper, polished to a mirror surface with a polishing machine, ultrasonically cleaned with ethanol and acetone respectively, dried, and transferred to a vacuum chamber. Pure Al was used as the target material and the vacuum degree was 5×10 -4 Under Pa, argon was used as the working gas at a flow rate of 40 sccm, and an Al layer with a thickness of 0.5 μm was obtained by magnetron sputtering to obtain NdFeB permanent magnet material A;

[0040] S2: The NdFeB permanent magnet material A was polished, washed, dried, and transferred to the deposition solution. The NdFeB permanent magnet material A was used as the cathode and the stainless steel plate was used as the anode. The distance between the cathode and the anode was 3 mm. At a temperature of 2 ° C and a voltage of 100 V, a TbF3 layer was electrophoretically deposited for 150 seconds. The material was washed, dried, and placed in a vacuum of 2.5×10 -3 The NdFeB permanent magnet material B is obtained by first heat treating at 860°C for 9 hours and then heat treating at 510°C for 2 hours; wherein, the preparation method of the deposition liquid is as follows: terbium fluoride and magnesium chloride are added to anhydrous ethanol and ultrasonically dispersed for 30 minutes to obtain a deposition liquid including 10 g / L terbium fluoride and 1.5 g / L magnesium chloride.

[0041] Comparative Example 2: Based on Example 1, only gallium is sputtered by magnetron sputtering without electroplating. The other processes remain unchanged, as follows:

[0042] S1: The outer surface of the NdFeB permanent magnet material was sanded to 2000 mesh with sandpaper, polished to a mirror surface with a polishing machine, ultrasonically cleaned with ethanol and acetone respectively, dried, and transferred to a vacuum chamber. Pure Ga was used as the target material and the vacuum degree was 5×10 -4 Under Pa, argon was used as the working gas at a flow rate of 40 sccm, and an Al-Ga layer with a thickness of 0.5 μm was obtained by magnetron sputtering to obtain NdFeB permanent magnet material A;

[0043] S2: The NdFeB permanent magnet material A was polished, washed, dried, and transferred to the deposition solution. The NdFeB permanent magnet material A was used as the cathode and the stainless steel plate was used as the anode. The distance between the cathode and the anode was 3 mm. At a temperature of 2 ° C and a voltage of 100 V, a TbF3 layer was electrophoretically deposited for 150 seconds. The material was washed, dried, and placed in a vacuum of 2.5×10 -3 The NdFeB permanent magnet material B is obtained by first heat treating at 860°C for 9 hours and then heat treating at 510°C for 2 hours; wherein the preparation method of the deposition liquid is to add terbium fluoride and magnesium chloride to anhydrous ethanol and ultrasonically disperse them for 30 minutes to obtain a deposition liquid including 10 g / L terbium fluoride and 1.5 g / L magnesium chloride;

[0044] Comparative Example 3: Based on Example 1, a TbF3 layer was directly electrophoretically deposited without electroplating. The remaining processes remained unchanged, as follows:

[0045] S1: The outer surface of the NdFeB permanent magnet material was sanded to 2000 mesh with sandpaper, polished to a mirror surface with a polishing machine, ultrasonically cleaned with ethanol and acetone respectively, dried, and transferred to the deposition liquid. With NdFeB permanent magnet material A as the cathode and stainless steel plate as the anode, the distance between the cathode and the anode was 3 mm, and a TbF3 layer was electrophoretically deposited at a temperature of 2°C and a voltage of 100 V for 150 seconds. After washing and drying, the layer was placed in a vacuum of 2.5×10 -3The NdFeB permanent magnet material B is obtained by first heat treating at 860°C for 9 hours and then heat treating at 510°C for 2 hours; wherein, the preparation method of the deposition liquid is as follows: terbium fluoride and magnesium chloride are added to anhydrous ethanol and ultrasonically dispersed for 30 minutes to obtain a deposition liquid including 10 g / L terbium fluoride and 1.5 g / L magnesium chloride.

[0046] Comparative Example 4: Based on Example 1, a TbF3 layer was first electrophoretically deposited, and then an aluminum layer was electrophoretically deposited. No electroplating treatment was performed, and the remaining processes remained unchanged, as follows:

[0047] S1: The outer surface of the NdFeB permanent magnet material was sanded to 2000 mesh with sandpaper, polished to a mirror surface with a polishing machine, ultrasonically cleaned with ethanol and acetone respectively, dried, and transferred to deposition liquid A, with NdFeB permanent magnet material A as cathode, stainless steel plate as anode, and the distance between cathode and anode was 3mm. At a temperature of 2°C and a voltage of 100V, a TbF3 layer was electrophoretically deposited for 150 seconds, washed, and dried; moved to deposition liquid B, with NdFeB permanent magnet material as cathode, stainless steel plate as anode, and the distance between cathode and anode was 3mm. At a temperature of 2°C and a voltage of 100V, an Al layer was electrophoretically deposited for 150 seconds, washed, dried, and vacuumed to 2.5×10 -3 The NdFeB permanent magnet material B is obtained by first heat treating at 860°C for 9 hours and then heat treating at 510°C for 2 hours; wherein, the preparation method of the deposition liquid A is to add terbium fluoride and magnesium chloride to anhydrous ethanol and ultrasonically disperse them for 30 minutes to obtain a deposition liquid including 10 g / L terbium fluoride and 1.5 g / L magnesium chloride; the preparation method of the deposition liquid A is to add aluminum powder and magnesium chloride to anhydrous ethanol and ultrasonically disperse them for 30 minutes to obtain a deposition liquid including 8 g / L aluminum powder and 1.5 g / L magnesium chloride.

[0048] Comparative Example 5: Based on Example 1, a TbF3 layer and an aluminum layer were electrophoretically deposited simultaneously without electroplating. The remaining processes remained unchanged, as follows:

[0049] S1: The outer surface of the NdFeB permanent magnet material was sanded to 2000 mesh with sandpaper, polished to a mirror surface with a polishing machine, ultrasonically cleaned with ethanol and acetone respectively, dried, and transferred to the deposition liquid. With NdFeB permanent magnet material A as the cathode and stainless steel plate as the anode, the distance between the cathode and the anode was 3 mm, and a TbF3 layer was electrophoretically deposited at a temperature of 2°C and a voltage of 100 V for 150 seconds. After washing and drying, the layer was placed in a vacuum of 2.5×10 -3 The NdFeB permanent magnet material is first heat treated at 860°C for 9 hours and then heat treated at 510°C for 2 hours; wherein the preparation method of the deposition liquid is to add terbium fluoride and magnesium chloride to anhydrous ethanol and ultrasonically disperse them for 30 minutes to obtain a deposition liquid including 10 g / L terbium fluoride, 8 g / L aluminum powder, and 1.5 g / L magnesium chloride;

[0050] Comparative Example 6: Based on Example 1, the thickness of the magnetron sputtering was increased, the electroplating treatment was not performed, and the other processes remained unchanged, as follows:

[0051] S1: The outer surface of the NdFeB permanent magnet material was sanded to 2000 mesh with sandpaper, polished to a mirror surface with a polishing machine, ultrasonically cleaned with ethanol and acetone respectively, dried, and transferred to a vacuum chamber. Al-Ga alloy (Al-Ga alloy includes 80wt% aluminum and the rest is gallium) was used as the target material. The vacuum degree was 5×10 -4 Under Pa, argon was used as the working gas at a flow rate of 40 sccm, and an Al-Ga layer with a thickness of 1 μm was obtained by magnetron sputtering to obtain NdFeB permanent magnet material A;

[0052] S2: The NdFeB permanent magnet material A was polished, washed, dried, and transferred to the deposition solution. The NdFeB permanent magnet material A was used as the cathode and the stainless steel plate was used as the anode. The distance between the cathode and the anode was 3 mm. At a temperature of 2 ° C and a voltage of 100 V, a TbF3 layer was electrophoretically deposited for 150 seconds. The material was washed, dried, and placed in a vacuum of 2.5×10 -3 The NdFeB permanent magnet material B is obtained by first heat treating at 860°C for 9 hours and then heat treating at 510°C for 2 hours; wherein the preparation method of the deposition liquid is to add terbium fluoride and magnesium chloride to anhydrous ethanol and ultrasonically disperse them for 30 minutes to obtain a deposition liquid including 10 g / L terbium fluoride and 1.5 g / L magnesium chloride;

[0053] S3: On the surface of NdFeB permanent magnet material B, the current density is 1.5A / dm 2 , electroplating at a temperature of 50°C for 30 minutes to form a NI-Co-Tb layer, and annealing at 510°C for 2 hours to obtain a nickel-plated modified NdFeB permanent magnet material; wherein the electroplating solution includes the following raw materials: 230g / L nickel sulfate hexahydrate, 36g / L nickel chloride hexahydrate, 46g / L cobalt sulfate heptahydrate, 10g / L terbium nitrate hexahydrate, 1g / L saccharin sodium, 20g / L potassium chloride, 30g / L boric acid, 0.1g / L sodium dodecyl sulfate, and the pH is 5.

[0054] Comparative Example 7: Based on Example 1, terbium was not introduced into the electroplating solution, and the rest of the process remained unchanged, as follows:

[0055] S1: The outer surface of the NdFeB permanent magnet material was sanded to 2000 mesh with sandpaper, polished to a mirror surface with a polishing machine, ultrasonically cleaned with ethanol and acetone respectively, dried, and transferred to a vacuum chamber. Al-Ga alloy (Al-Ga alloy includes 80wt% aluminum and the rest is gallium) was used as the target material. The vacuum degree was 5×10 -4 Under Pa, argon was used as the working gas at a flow rate of 40 sccm, and an Al-Ga layer with a thickness of 0.5 μm was obtained by magnetron sputtering to obtain NdFeB permanent magnet material A;

[0056] S2: The NdFeB permanent magnet material A was polished, washed, dried, and transferred to the deposition solution. The NdFeB permanent magnet material A was used as the cathode and the stainless steel plate was used as the anode. The distance between the cathode and the anode was 3 mm. At a temperature of 2 ° C and a voltage of 100 V, a TbF3 layer was electrophoretically deposited for 150 seconds. The material was washed, dried, and placed in a vacuum of 2.5×10 -3 The NdFeB permanent magnet material B is obtained by first heat treating at 860°C for 9 hours and then heat treating at 510°C for 2 hours; wherein the preparation method of the deposition liquid is to add terbium fluoride and magnesium chloride to anhydrous ethanol and ultrasonically disperse them for 30 minutes to obtain a deposition liquid including 10 g / L terbium fluoride and 1.5 g / L magnesium chloride;

[0057] S3: On the surface of NdFeB permanent magnet material B, the current density is 1.5A / dm 2 , electroplating at a temperature of 50°C for 30 minutes to form a NI-Co-Tb layer, and annealing at 510°C for 2 hours to obtain a nickel-plated modified NdFeB permanent magnet material; wherein the electroplating solution includes the following raw materials: 230g / L nickel sulfate hexahydrate, 36g / L nickel chloride hexahydrate, 46g / L cobalt sulfate heptahydrate, 1g / L saccharin sodium, 20g / L potassium chloride, 30g / L boric acid, 0.1g / L sodium dodecyl sulfate, and the pH is 5.

[0058] Performance test: (1) The coercive force and performance of the samples prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were measured using a permanent magnet material precision measurement system; (2) The samples prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were subjected to electrochemical tests using a CS350H electrochemical workstation. The sample size was 10 mm × 10 mm × 5 mm, the auxiliary electrode was a Pt electrode, the reference electrode was a saturated calomel electrode, the solution was a 3.5 wt % NaCl solution, the scanning range was ±0.25 V relative to the open circuit potential, the scanning speed was 0.5 mV / s, and the test temperature was 25°C. The experimental data are shown in the following table.

[0059] Group Coercive force (kOe) Remanence (kGs) <![CDATA[Corrosion current (μA / cm 2 ).]]> Example 1 21.25 14.65 0.34 Example 2 21.14 14.42 0.47 Example 3 20.89 14.49 0.52 Comparative Example 1 18.42 14.04 3.12 Comparative Example 2 17.84 14.24 2.74 Comparative Example 3 16.57 13.95 7.81 Comparative Example 4 19.78 14.42 6.78 Comparative Example 5 19.14 14.36 7.12 Comparative Example 6 15.74 13.75 2.47 Comparative Example 7 20.12 14.33 0.92 Initial magnet 14.12 14.78 38.24

[0060] Conclusion: As can be seen from Table 1, the present invention significantly improves the magnetic properties and corrosion resistance of the permanent magnet material by sequentially magnetron sputtering an Al-Ga layer, electrophoretically depositing a TbF3 layer, and electroplating a NI-Co-Tb layer on the surface of the NdFeB permanent magnet material.

[0061] Among them, in Comparative Example 1, magnetron sputtering only sputters aluminum, lacks the refining effect of gallium, and the magnetic properties are reduced; in Comparative Example 2, magnetron sputtering only sputters gallium, the diffusion depth is limited, and the coercive force performance is reduced; in Comparative Example 3, the TbF3 layer is directly electrophoretically deposited, lacks the promotion effect of Al-Ga, the diffusion depth is low, the magnetic properties are reduced, and because there is no protection of the Al-Ga layer, the magnet absorbs hydrogen ions in the deposition solution, resulting in a decrease in corrosion resistance; in Comparative Example 4, the TbF3 layer is electrophoretically deposited first, and then the aluminum layer is electrophoretically deposited, the diffusion depth and uniformity of the terbium element are reduced, and the magnetic properties are not as good as those in Example 1; In comparative example 5, the TbF3 layer and the aluminum layer are electrophoretically deposited at the same time. Due to the poor compatibility between aluminum and magnets in electrophoretic deposition, the aluminum falls off under the action of gravity. In essence, the TbF3 layer is deposited first and then the aluminum layer is electrophoretically deposited. Therefore, the magnetic properties are not as good as those in Example 1, and due to the influence of aluminum, the overall coating is uneven, and the performance is further reduced compared with comparative example 4; in comparative example 6, the thickness of magnetron sputtering is increased, the diffusion rate of elemental terbium is greatly reduced, and the diffusion depth is affected, and the magnetic properties are reduced; in comparative example 7, terbium is not introduced into the electroplating solution, the coating density is not as good as that in Example 1, and the corrosion resistance is reduced.

[0062] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art will be able to modify the technical solutions described in the aforementioned embodiments or substitute equivalents for some of the technical features. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.

Claims

1. A method for preparing a nickel-plated modified NdFeB permanent magnet material, characterized in that: The following steps are involved: S1: grinding, polishing, washing, drying, and magnetron sputtering Al-Ga layers on the NdFeB permanent magnet material to obtain NdFeB permanent magnet material A; S2: grinding, washing, drying, electrophoretically depositing a TbF3 layer on the NdFeB permanent magnet material A, and performing thermal diffusion treatment to obtain the NdFeB permanent magnet material B; S3: Electroplating a NI-Co-Tb layer on the surface of the NdFeB permanent magnet material B to obtain a nickel-plated modified NdFeB permanent magnet material.

2. The method for preparing a nickel-plated modified NdFeB permanent magnet material according to claim 1, wherein: During the magnetron sputtering process, the target material is Al-Ga alloy, and the vacuum degree is 5×10 -4 Pa, the working gas is argon, the flow rate is 35~45sccm, and the coating thickness is 0.4~0.6μm.

3. The method for preparing a nickel-plated modified NdFeB permanent magnet material according to claim 2, wherein: The Al-Ga alloy includes 75-85 wt % of aluminum and the remainder is gallium.

4. The method for preparing a nickel-plated modified NdFeB permanent magnet material according to claim 1, wherein: During the electrophoretic deposition process, the deposition solution includes the following raw materials: 10-12 g / L terbium fluoride, 1-1.5 g / L magnesium chloride, and the solvent is ethanol.

5. The method for preparing a nickel-plated modified NdFeB permanent magnet material according to claim 1, wherein: During the electrophoretic deposition process, the NdFeB permanent magnet material A is the cathode, the stainless steel plate is the anode, the distance between the cathode and the anode is 3 mm, the temperature is 25-30° C., the voltage is 100 V, and the time is 140-160 seconds.

6. The method for preparing a nickel-plated modified NdFeB permanent magnet material according to claim 1, wherein: During the thermal diffusion process, the specific process is as follows: -3 Under the conditions of 850~875℃ for 9~9.5h, then heat treat at 500~520℃ for 1.5~2h.

7. The method for preparing a nickel-plated modified NdFeB permanent magnet material according to claim 1, wherein: During the electroplating process, the electroplating solution includes the following raw materials: 220-240 g / L nickel sulfate hexahydrate, 35-40 g / L nickel chloride hexahydrate, 44-48 g / L cobalt sulfate heptahydrate, 10-12 g / L terbium nitrate hexahydrate, 1-1.5 g / L saccharin sodium, 18-22 g / L potassium chloride, 28-30 g / L boric acid, 0.1-0.2 g / L sodium dodecyl sulfate, and a pH of 4.5-5.

5.

8. The method for preparing a nickel-plated modified NdFeB permanent magnet material according to claim 1, wherein: During the electroplating process, the current density is 1.5~2A / dm 2 , time is 25~30min, temperature is 45~50℃.

9. Nickel-plated modified NdFeB permanent magnet material prepared according to the method for preparing a nickel-plated modified NdFeB permanent magnet material according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Method for improving performance of neodymium-iron-boron magnet and high-coercivity neodymium-iron-boron magnet

    CN116544022A

  • Corrosion-resistant multi-coating neodymium iron boron and preparation process

    CN106710767A

  • Composition for infiltration treatment of sintered oriented magnet, use and method thereof

    CN108962524A

  • Modified sintered neodymium-iron-boron magnet, and preparation method and application thereof

    CN113936877A

  • Grain boundary diffusion method for sintered neodymium-iron-boron magnet

    CN115064376A